Bullous pemphigoid induced by m‐TOR inhibitors in renal transplant recipients. (29th August 2014) - Atzori, L.; Conti, B.; Zucca, M.; Pau, M.
Abstract Background Bullous pemphigoid (BP) is an acquired autoimmune disease, with typical histology and immune pathological findings, which might be associated with drug therapy. The list of responsible drugs increases every year, but a current literature revision do not include the mammalian target of rapamycin (mTOR) inhibitors. By converse, bullous pemghigoid cases have been described in renal transplant recipients and associated with the allogenic graft itself, causing a cross reaction against the skin, or unbalancing the immune response, through a chronic cell‐mediated suppression, non‐specifically favouring the autoantibody production. Object and results Two cases of BP occurred, respectively, 10 days to 2 months after the addition to their current regimen of everolimus in a 35‐year‐old woman and sirolimus in a 65‐year‐old man. The graft functionality was within normal range. General corticosteroids therapy resistance, immediate improvement after drug discontinuation (dechallenge) and relapse after re‐exposure (rechallenge) were striking criteria supporting a causative role of the drugs, grouped in the mTOR inhibitors class. Conclusions The diagnosis of drug‐induced events is crucial for early management, and particularly bullous eruptions affect patients' health and quality of life. Additional research is necessary to confirm the m‐TOR inhibitors association, which exploit the possible mechanisms and eventually point out preventive measures.